Risk Factors for Non-communicable Diseases among Adults of 25-65 Years at Kakamega County General Hospital, Kenya - Monicah Njambi Kibe; Gordon Nguka; Silvenus Konyole (Intelektual Pustaka Media Utama, 2018)
In Kenya the growing number of premature deaths with half of all hospital admissions and 33% of all deaths are associated with Non-communicable diseases. The study determined the physical measurements and lipid parameters of adults 25-65 years at Kakamega County General Hospital. Data was collected using the WHO STEPs Instrument: Physical measurements assessed were Mid Upper Arm Circumference, Waist Hip measurements, Body mass Index and blood pressure. The study significance level was 0.05. Data was analyzed using SPSS version 20. Descriptive statistics was used. χ2 test of independence was used to find out the relationship between anthropometric measurements and lipid parameters. Data was presented in form of tables, figures and texts. There was a significant relationship between BMI and Triglycerideχ2 (12, N=60)= 25.752 P=0.012, BMI and LDLχ2(8,N=60)=19.312 p=0.013, BMI and Total Cholesterol χ2(8, N=60)=18.694 p=0.017, MUAC and HDL χ2(4, N=60) =14.446 p=0.006, WHR and Total Cholesterol χ2(2, N=60)=17.985 p=0.000, WHR and LDL χ2(2, N=60)=15.246p=0.000. The study advocated for policies to reduce the incidences of risk factors for NCDs which will assist in achievement of Sustainable Development Goals. Kenyan population are in need of screening for risks associated with NCDs.